Custos logísticos de transporte: uber como meio de mobilidade urbana - Momes, James de Melo (2023)
Logistic transport is an extremely important factor that moves a large portion of the population daily, thinking about it companies began to invest in different strategies to take passengers to their desired locations in the best way, using the most current technology, developing applications that integrate drivers and passengers. This opportunity generated income for people, and at the same time proved to be a new way of getting around in addition to public transport. With that in mind, this work was developed seeking to better detail the costs that a person has when providing this transport service, using their own or rented vehicles, in the city of Manaus - Am this means of mobility proved to be quite effective even with the lack of infrastructure is fuel with sky-high prices. It was possible to analyze that the drivers did not pay attention to other costs of this transport, so through this research the costs and the real profit margin were identified. As a result, this work guides the driver before making any trip to calculate his expenses based on the km that will be traveled, in this way it is necessary to understand what the expenses are so that profit can be obtained with this form of work